Business Strategy Analysis of PT Kalbe Farma Tbk Using Strategic Management Approach - Wati, Annisa Mahdia; R. Murhadi, Werner (Dinasti Publisher, 2025)
This article aims to analyze the business strategy of PT Kalbe Farma Tbk, the largest integrated pharmaceutical company in Indonesia, in responding to the dynamics of the competitive and evolving pharmaceutical industry. This study applies a qualitative approach with a case study method based on secondary data, including company annual reports and strategic management literature. The analytical tools used include PESTEL, Porter’s Five Forces, Product Life Cycle, SWOT, Value Chain, and strategic matrices such as SWOT, SPACE, IE, BCG, and the Grand Strategy Matrix. The results show that Kalbe’s strengths lie in brand reputation, product diversification, and an extensive distribution network, with opportunities arising from digitalization trends and increased public health awareness. The recommended strategies are product development, market development, and forward integration. These strategies are deemed most appropriate based on the QSPM results and are expected to help Kalbe maintain its market leadership while achieving sustainable international expansion.